2016
DOI: 10.24924/ijelt/2016.11/v1.iss1/14.21
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Media on Students’ Academic

Abstract: Social media are web-based services that gives individual the opportunity to create either a public or semi-public profile within a bounded system, add a list of others to with they share a connection and view and transvers their list of connections and those made by others within the system. Therefore, this study was carried out with the aim of examining the impact of use of social media on students' academic performance in Malaysian Tertiary Institution. In other to measure social media platforms a questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 3 publications
3
17
1
1
Order By: Relevance
“…The results of the second hypothesis test showed that the nature of use of social media is insignificant. This result contradicts the findings of previous work such as Mensah & Nizam (2016) who found a significant impact of nature of use of social media on students' academic performance. The reasons behind using social media diverse including academic and non-academic purposes such as sharing information, socializing, contacting friends, downloading music and videos…etc.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results of the second hypothesis test showed that the nature of use of social media is insignificant. This result contradicts the findings of previous work such as Mensah & Nizam (2016) who found a significant impact of nature of use of social media on students' academic performance. The reasons behind using social media diverse including academic and non-academic purposes such as sharing information, socializing, contacting friends, downloading music and videos…etc.…”
Section: Discussioncontrasting
confidence: 99%
“…This result is consistent with the findings of Queder & Abousaber (2018). The most contributing factor in predicting academic performance was duration of use, followed by appropriateness of use; matching the results of other previous studies (Mensah & Nizam, 2016;Lambić,2016;Ainin et al, 2015). Whereas the results contradict the findings of the majority of previous work which either indicated a negative relationship between the use of social media and students' academic performance such as (Liu et al, 2017;Janković et al, 2015), those research where no significant relationship was found like Lau (2017), Rahman & Stephen (2016) and Rashid & Asghar (2016).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Overall, these results, showing improvements in L2 skills combined with a mixture of positive and ambivalent attitudes to SNS use in language learning, reflected results from similar studies carried out in other parts of the world (Bosch, 2009;Selwyn, 2009;Ahmed & Qazi, 2011;Yunus, Salehi, & Chenzi, 2012;Kamnoetsin, 2014;Mensah & Nizam, 2016) and in other Arabic-speaking countries (Alfaki & Alharthy, 2014).…”
Section: Discussionsupporting
confidence: 73%
“…In contrast, other studies showed a negative effect of social media usage on the academic performance of university students. Students who spent much time on social media platforms for chatting had a high probability of experiencing a decline in their academic performance 11, 12, 13. In addition, students who were deeply involved in the activities of networking sites during study lacked attention and were distracted 11 .…”
Section: Introductionmentioning
confidence: 99%